Diversity of types of new economy and approaches to their study - Shcherbin, Vyacheslav K. (Journal of the Belarusian State University. Sociology, 2024)
The article discusses the latest types of economic systems: virtual, green, intellectual, information, cognitive, narrative, knowledge-intensive, noospheric, behavioural, network, systemic, smart, digital, glamour, knowledge, Internet, post-knowledge economies, etc. The relationships of these types of economic systems with each other are analysed. The possibilities of political economy and economic sociology for studying the complex phenomenon of the new economy are determined. The following conclusions are substantiated: today a new economy is actively developing in Belarus (primarily intellectual, information, network, smart, digital, knowledge economies); the most promising type of new economy for the further development of Belarus is the intellectual economy; the processes of scientific learning and intellectualisation of various branches of production and social spheres of life of Belarusian society that underlie the intellectual economy should be complemented by the measures for industrialisation and reindustrialisation of its industry and agriculture, and accelerated development of culture, science and education.
Keywords: new economy and its types; intellectualisation of production and society; intellectual state; political economy; economic sociology